Perspectives of onion hybrid breeding in India: An overview - SINGH, HIRA; KHAR, ANIL (The Indian Journal of Agricultural Sciences, 2021)
Onion (Allium cepa L.), a major member of monocot family Amaryllidaceae, is an important bulbous vegetable cropused in almost every Indian kitchen. Being cultivated since antiquity, farmers rely on growing open pollinated varietiessince hybrid development in this crop has not gained pace. Among important vegetables, F1 hybrid developmentremains underutilized in onion especially in India and other developing countries as compared to other onion growingcountries. Development of commercial hybrids in onion principally depends on the availability of suitable inbredlines against the backdrop of stable male sterile system. The future scope of commercial onion hybrids needs to befocused comprehensively for the identification of male sterile lines from Indian onion population by utilizing modernbiotechnological tools. Molecular markers distinguishing cytoplasm and linked to restorer of male sterility, Ms locus,are important. Release of commercial hybrids from public sector would play a great role for breaking yield barriers andsignificant enhancement of productivity of onion under changing climate scenario and increasing domestic demand.